Investigation on Physical and Mechanical Characteristics of Date Palm Fiber Reinforced Aliphatic Epoxy Hybrid Composites - Mohamad Reda A. Refaai; R. Meenakshi Reddy; M. Indra Reddy; B. Shahul Hamid Khan; V. Nagaraju; S. Praveen Kumar (Advances in Polymer Technology)
Automotive industry attention in using date palm fiber as an internal material has been sparked by its use as a polymer reinforced composite. Date palm fiber-reinforced aliphatic epoxy composites for semistructural applications are the key goals of this work. To make the various composites, they used a combination of manual lay-up and adhesive bonding. Date palm fiber/bamboo hybrid composite and uncontaminated composites were tested through density, tensile, flexural, and impact tests and also studied the effects of swelling, water absorption, and physical performance in greater depth. According to studies, hybrid composites constructed from date palm fiber and bamboo had the best mechanical properties. The date palm/bamboo hybrid composite was created to impact the toughness of 12.72 J/m in tensile, flexural strength, and impact toughness measurements. The reduced swelling and water absorption were 27.66 percent and 15.37 percent, respectively, when testing a date palm fiber/bamboo hybrid composite. Density ranged from 1.15 g/cm3 to 1.25 g/cm3 for bamboo fiber composite material and from 1.23 to 1.27 g/cm3 for date palm fiber/bamboo composite material. High flexural strength is achieved by the bamboo composite specimen (bamboo: 6.18 MPa), followed by (PDF-A/B: 61.12 MPa, date palm fiber-AA/B: 61.08 MPa, date palm fiber-L/B: 60.82 MPa, and date palm fiber-G/B: 61.47 MPa), and the PDF composite specimens (date palm fiber-A/B: 61.112). Hybridized materials (date palm fiber/bamboo fiber) with a 50 : 50 ratio had higher impact strength.